Factors Associated with Lymph Node Metastasis in Special Types of Invasive Breast Cancer at National Cancer Hospital in the Period of 2018 - 2021 - Thi Quynh, Nguyen; Quang Dien, Trinh (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2021)
This paper assesses the rate of lymph node metastasis and the correlation between lymph node metastasis and some pathological characteristics in special types of invasive breast cancer. In the paper, a descriptive cross‐sectional study was conducted on 200 patients with special types of invasive breast cancer at the Institute of Molecular Biology and Pathology - National Cancer Hospital from August 2020 to April 2021. The study results show that 32% of the 200 cases had nodal metastases. The factors associated with the increased risk of lymph node metastasis were of histological types (invasive lobular, invasive micropapillary carcinomas) (p = 0.000), high tumour grade (p = 0.000), the presence of lymphovascular invasion (p = 0.000), tumor-infiltrating lymphocytes (TILs) < 10% (p = 0.000), the presence of tumor necrosis (p = 0.001), Her-2/neu overexpression (p = 0.01), Ki-67 ≥ 20% (p = 0.036), HER2-positive breast cancer (p = 0.015).  Overall, the rate of lymph node metastasis was 32%. Histological type, tumour grade, the presence of lymphovascular invasion, TILs, tumor necrosis, Her-2/neu and Ki-67 expression, and molecular subtype were factors related to lymph node metastasis in special types of invasive breast cancer. Keywords: Lymph node metastasis, invasive breast cancer, special types. References [1] World Health Organization, Breast Tumors (5th ed), International Agency for Research on Cancer, Lyon, France, 2019. [2] K. M. Masters, S. L.Wong, R. C. Martin et al., Dermal Injection of Radioactive Colloid Is Superior to Peritumoral Injection for Breast Cancer Sentinel Lymph Node Biopsy: Results of A Multiinstitutional Study, Annals of Surgery, Vol. 233, No. 5, 2001, pp. 676, https://doi.org/10.1097/00000658-200105000-00012. [3] A. V. Ashturkar, G. S. Pathak, S. D. Deshmukh, H. T. Pandave, Factors Predicting the Axillary Lymph Node Metastasis in Breast Cancer: Is Axillary Node Clearance Indicated in Every Breast Cancer Patient? Indian Journal of Surgery, Vol. 73, No. 5,2011, pp. 331-335, https://doi.org/10.1007/s12262-011-0315-5. [4] M. R. Peter, D. L.Michelino, V. Tricia et al., Prediction of Axillary Lymph Node Status in Breast Cancer Patients by Use of Prognostic Indicators, JNCI: Journal of the National Cancer Institute, Vol. 86, No. 23, 1994, pp. 1771-1775, https://doi.org/10.1093/jnci/87.8.607. [5] R. Salgado, C. Denkert, S. Demaria et al., The Evaluation of Tumor-Infiltrating Lymphocytes (TILs) in Breast Cancer: Recommendations by An International TILs Working Group 2014, Annals of Oncology, Vol. 26, No. 2, 2015, pp. 259-271, https://doi.org/10.1093/annonc/mdu450. [6] K. H. Young, Statistical Notes for Clinical Researchers: Chi-Squared Test and Fisher's Exact Test, Restorative Dentistry & Endodontics, Vol. 42, No. 2, 2017, pp. 152-155, https://doi.org/10.5395/rde.2017.42.2.152. [7] L. G. L. Tan, Y. Y. Tan, D. Heng, M. Y. Chan, Predictors of Axillary Lymph Node Metastases in Women with Early Breast Cancer in Singapore, Singapore Med J, Vol. 46, No. 12, 2005, pp. 693, https://doi.org/10.1016/s0959-8049(98)80134-2. [8] A. Barth, P. H. Craig, M. J. Silverstein, Predictors of Axillary Lymph Node Metastases in Patients with T1 Breast Carcinoma, Cancer, Vol. 79, No. 10, 1997, pp. 1918-1922, https://doi.org/10.1002/(SICI)10970142(19970515) 79:10<1918::AID-CNCR12>3.0.CO;2-Y. [9] Y. Iwasaki, Axillary Node Metastasis from T1N0M0 Breast Cancer: Possible Avoidance of Dissection in A Subgroup, Japanese Journal of Clinical Oncology, Vol. 28, No. 10, 1998, pp. 601-603, https://doi.org/10.1093/jjco/28.10.601. [10] G. Viale, S. Zurrida et al., Predicting the Status of Axillary Sentinel Lymph Nodes in 4351 Patients with Invasive Breast Carcinoma Treated in A Single Institution, Cancer, Vol. 103, No. 3, 2005, pp. 492-500, https://doi.org/10.1002/cncr.20809. [11] S. K. Çetintaş, M. Kurt et al., Factors Influencing Axillary Node Metastasis in Breast Cancer, Tumori Journal, Vol. 92, No. 5, 2006, pp. 416-422, https://doi.org/10.1177/030089160609200509. [12] T. V. To, A Study of Morphology, Immunohistochemistry and Their Prognostic Value in Breast Carcinoma, Ph.D Dissertation, Hanoi Medical University, Hanoi, 2004 (in Vietnamese). [13] R. Lauria, F. Perrone et al., The Prognostic Value of Lymphatic and Blood Vessel Invasion in Operable Breast Cancer, Cancer, Vol 76, No. 10, 1995, pp. 1772-1778, https://doi.org/10.1002/1097-0142(19951115)76 :10<1772::AID-CNCR2820761014>3.0.CO;2-O. [14] R. Yerushalmi, M. M. Hayes, K. A. Gelmon, Breast Carcinoma - Rare Types: Review of the Literature, Annals of Oncology, Vol. 20, No. 11, 2009, pp. 1763-1770, https://doi.org/10.1093/annonc/mdp245. [15] A. Caziuc, D. Schlanger, G. Amarinei, Can Tumor-Infiltrating Lymphocytes (TILs) Be a Predictive Factor for Lymph Nodes Status in Both Early Stage and Locally Advanced Breast Cancer?, Vol. 8, No. 5, 2019, pp. 545, https://doi.org/10.3390/jcm8040545. [16] K. Takada, S. Kashiwagi, Y. Asano, Prediction of Lymph Node Metastasis by Tumor-Infiltrating Lymphocytes in T1 Breast Cancer, BMC Cancer, Vol. 20, No. 1, 2020, pp. 598, https://doi.org/10.1186/s12885-020-07101-y. [17] N. T. Ha, Evaluation of Axillary Lymph Node Status and Vascular Infiltration by Molecular Type of Breast Carcinoma, Master Thesis, Hanoi Medical University, Hanoi, 2018 (in Vietnamese). [18] J. Makki, Diversity of Breast Carcinoma: Histological Subtypes and Clinical Relevance, Clinical Medicine Insights: Pathology, Vol. 8, 2015, pp. 23-31, https://doi.org/10.4137/cpath.s31563. [19] L. A. Carey et al, Breast Cancer Subtypes, and Survival in the Carolina Breast Cancer Study, JAMA, Vol. 295, No. 21, 2006, pp. 2492, https://doi.org/10.1001/jama.295.21.2492.